The ESID online clinical and research database - Knerr, Viviane; Gathmann, Benjamin; Eades-Perner, Anne-Marie; Kindle, Gerhard; Veit, Dominic; Guzman, David; Grimbacher, Bodo (Central European Journal of Immunology, 2005)
The ESID online database has been set up by the European Society for Immunodeficiencies in order to provide detailed long term documentation of data about patients with primary immunodeficiencies. Its aim is to improve diagnosis, therapy and prognosis of PID patients by enabling large genetic and therapeutic trials. The database is capable of collecting therapy and laboratory data on almost 180 different primary immunodeficiencies with a common core dataset and additionally offers large disease-specific data models for a number of diseases which expands constantly. The project involves numerous documenting centres throughout Europe and is being supported by the European Union and pharmaceutical companies. One of the advantages of the system is the easy handling which does not require technical premises on site. The database can be accessed online and is password protected.